2007
DOI: 10.1176/foc.5.2.foc240
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Therapies for Drug Abuse

Abstract: The past three decades have been marked by tremendous progress in behavioral therapies for drug abuse and dependence, as well as advances in the conceptualization of approaches to development of behavioral therapies. Cognitive behavior therapy, contingency management, couples and family therapy, and a variety of other types of behavioral treatment have been shown to be potent interventions for several forms of drug addiction, and scientific progress has also been greatly facilitated by the articulation of a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 92 publications
(37 reference statements)
1
61
0
2
Order By: Relevance
“…Family and relational treatments have already demonstrated effectiveness in treating depressive and anxiety disorders [10, 27]. Further, couple and family therapy have demonstrated utility as an intervention for multiple forms of drug addiction [28], including alcohol abuse [29]. A meta-analysis of treatments for drug abuse found that family therapy was more effective than individual therapy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Family and relational treatments have already demonstrated effectiveness in treating depressive and anxiety disorders [10, 27]. Further, couple and family therapy have demonstrated utility as an intervention for multiple forms of drug addiction [28], including alcohol abuse [29]. A meta-analysis of treatments for drug abuse found that family therapy was more effective than individual therapy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Switching to a different class of dopamine agonist may cause a relapse of ICDs. Therefore, close monitoring and a multidisciplinary approach to treatment should be encouraged, and behavioural therapies are receiving empirical support in non-PD populations 68 69…”
Section: Management Of Icds In Patients With Pdmentioning
confidence: 99%
“…Despite dramatic advances in the development of efficacious treatments for SUDs (Carroll & Onken, 2005), the utilization of evidence-base practices (EBPs) in routine SUD treatment remains limited. One recent suggestion to foster adoption of EBPs is that more studies be conducted with immediate relevance to clinicians and policy makers (Zerhouni, 2003).…”
Section: Practical Clinical Trials (Pcts)mentioning
confidence: 99%